Efficacy and safety of traditional Chinese medicine adjuvant therapy for severe pneumonia: evidence mapping of the randomized controlled trials, systematic reviews, and meta-analyses - Xie, Kai; Guan, Shengnan; Jing, Hui; Ji, Wenshuai; Kong, Xinxin; Du, Shen; Jia, Mingyan; Wang, Haifeng (Frontiers in Pharmacology, 2023)
Background and Objective: This study aims to identify, describe, assess, and summarize the currently available high-quality design evidence on TCM adjuvant therapy for severe pneumonia through the evidence mapping approach and to identify evidence gaps. Methods: Systematic searches were performed on English and Chinese online databases to identify papers from inception until August 2023 for inclusion into review. Randomized Controlled Trials (RCTs), Systematic Reviews (SRs), and meta-analyses concerning TCM adjuvant therapy for severe pneumonia or its complications in adults were included. A bubble plot was designed to visually display information in four dimensions. Results: 354 RCTs and 17 SRs or meta-analyses met the inclusion criteria. We found that TCM combined with conventional treatment could improve clinical total effective rate and TCM syndromes efficacy, as well as shorten mechanical ventilation time, infection control time, length of hospital and ICU stay, and significantly reduce temperature, respiratory rate, heart rate, white blood cell counts, levels of C-reactive protein, procalcitonin, blood inflammatory factors, bacteriological response, and D-dimer, in addition, decrease CPIS, APACHE II score, and PSI score, moreover, improve pulmonary imaging features, arterial blood gas indicators (including arterial oxygen pressure, arterial oxygen saturation, oxygen index), and lung function (including forced vital capacity, forced expiratory volume in the first second) for severe pneumonia compared with single conventional treatment (P<0.05), and there was no significant difference in adverse reactions and incidence of adverse events (P>0.05). In addition, compared with single conventional treatment, most SRs or meta-analyses found that TCM combined with conventional treatment were "Beneficial" or "Probably beneficial" conclusion. TCM combined with conventional treatment had advantages in efficacy, clinical signs, laboratory results, and life quality outcomes of severe pneumonia, with no difference in safety outcomes, compared with single conventional treatment. QingJin Huatan Decoction is considered to be the most promising target, and Xuanbai Chengqi decoction also be "Probably beneficial" conclusion. XueBiJing Injection and TanReQing Injection are two commonly used Chinese herbal injections for treating severe pneumonia, and both are thought "Probably beneficial". Whereas, there was more need for multi-center, large sample sizes and high methodological quality RCTs in the future.